(untitled) (Swiss Medical Weekly, 2014)
STUDY OBJECTIVE: Hospital preparedness is an essential component of any developed health care system. However, there is no national legislation in Switzerland. The objective of this inquiry was to establish the geographic distribution, availability and characteristics of hospital preparedness across Switzerland. METHODS: A questionnaire regarding hospital preparedness in 2006 was addressed to all heads responsible for emergency departments (ED). The survey was initiated in 2007 and finalised in 2012. RESULTS: Of the 138 ED, 122 (88%) returned the survey. Eighty nine EDs (82%) had a disaster plan. CONCLUSIONS: Our study identified an insufficient rate of hospitals in which emergency physicians reported a disaster plan. The lack of national or cantonal legislation regulating disaster preparedness may be partially responsible for this.